Acquired white matter injury: Infection and inflammatory processes - Beckwith, Travis; Cecil, Kim M. (Journal of Pediatric Neuroradiology, 2013)
This article reviews the literature for neuroimaging features found in the pediatric population associated with infectious processes, specifically those with bacterial, fungal and parasitic origins. Magnetic resonance imaging is performed in patients with infectious and inflammatory disorders to further characterize involvement, especially within the white matter, assess for ischemia or poor response to pharmacologic therapy in a worsening clinical presentation, and assess for complications.
Keywords: Cytomegalovirus; enterovirus 71; Epstein-Barr; herpes simplex; human immunodeficiency virus; rubella; abscess; neurocysticercosis; toxoplasmosis